The formation of the university space in Kyiv (the history of the first facilities of the University of St. Volodymyr) - Самчук, Т. (Київський національний університет імені Тараса Шевченка, 2016)
This paper focuses on history of the St. Volodymyr University's first facilities in context of the formation of a special university space. We highlitened peculiarities in construction of these first buildings, their situation within the city space of Kyiv based on many archive and cartographical sources. The unknown archived documents were used in the article. We addressed to Samoilovich's, Achte's, Gudum-Levkovich's, Buchteev's houses; Begichev's yard and manege for hourse riding. We analyzed details of lease contracts of St. Volodymyr University's buildings. The article indicates which collections and departments were located in each of the leased buildings. The main conclusions show that university space covered big yards not only buildings. The facilities of university were concentrated in prestigious and aristocratic city's districts – Lypky and Pechersk. The history of other university buildings are to be described in papers to follow.

Розглянуто історію перших приміщень Університету св. Володимира в контексті формування університетського простору в Києві. Висвітлено подробиці будівництва будинків орендованих університетом і встановлено місце їхнього розташування в міському просторі Києва. Для цього були широко використані архівні й картографічні джерела. У публікації розглянуто історію таких університетських будівель і територій: будинок Самойловича, Ахте, Гудим-Левковича, Бухтєєва, садиба Бєгічева й манеж для верхової їзди. Проаналізовано деталі орендних договорів щодо найму будинків для Університету св. Володимира. Вказано, які колекції та структурні підрозділи університету розташовувалися в кожному з орендованих будинків. Головні висновки вказують на те, що університетський простір включав не лише будівлі, а й значні за площею орендовані садиби з рядом господарських приміщень. Будівлі Університету св. Володимира розташовувалися поруч із тогочасним адміністративним центром міста й губернії у престижних, аристократичних районах Києва – Липках і Печерську.
Формування університетського простору в Києві (до історії перших будинків університету св. Володимира)
Keywords: university space; Kyiv; University of St. Volodymyr; університетський простір; Київ; Університет св. Володимира